Book Review: National political elites, European integration and the eurozone crisis - Chiru, M (UACES, 2019)
The book draws on surveys of national legislators to analyse whether and how the economic crisis has changed the elites' levels of identification with the European Union, their perceptions of the functioning of the EU and their preferences for further integration and the future of the EU.